2015
DOI: 10.4081/ejtm.2015.4832
|View full text |Cite
|
Sign up to set email alerts
|

Persistent muscle fiber regeneration in long term denervation. Past, present, future

Abstract: Despite the ravages of long term denervation there is structural and ultrastructural evidence for survival of muscle fibers in mammals, with some fibers surviving at least ten months in rodents and 3-6 years in humans. Further, in rodents there is evidence that muscle fibers may regenerate even after repeated damage in the absence of the nerve, and that this potential is maintained for several months after denervation. While in animal models permanently denervated muscle sooner or later loses the ability to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…However, the terminal differentiation of the cells may be lacking as the myonuclear number continues to decrease (Dupont-Versteegden et al 1999). Other rat models of skeletal muscle atrophy, such as lower motor neuron injury and denervation, also lead to activation of satellite cells followed by inefficient differentiation and underdeveloped myotubes, with deficient or absent contractile machinery (Carraro et al 2015). Similar mechanisms, through activation and inefficient differentiation, may be responsible for the reduction of the satellite cell pool in the skeletal muscle of spinal cord-injured individuals (Verdijk et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the terminal differentiation of the cells may be lacking as the myonuclear number continues to decrease (Dupont-Versteegden et al 1999). Other rat models of skeletal muscle atrophy, such as lower motor neuron injury and denervation, also lead to activation of satellite cells followed by inefficient differentiation and underdeveloped myotubes, with deficient or absent contractile machinery (Carraro et al 2015). Similar mechanisms, through activation and inefficient differentiation, may be responsible for the reduction of the satellite cell pool in the skeletal muscle of spinal cord-injured individuals (Verdijk et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Denervation of rat skeletal muscle leads to formation of new myotubes with defective contractile machinery (Carraro et al. ). Skeletal muscle satellite cells from individuals with amyotrophic lateral sclerosis have reduced differentiation capacity and form myotubes with abnormal morphology (Pradat et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, CMAP recordings showed that these anatomically re-established NMJs are incapable of triggering normal muscle electrical activation, the key step in driving contraction, while the anatomy of the muscle itself does not show gross anatomical signs of atrophy. Previous studies have shown that muscles can still contract even after prolonged denervation periods (Ashley et al, 2007;Carraro et al, 2015). One limitation of CMAP recordings is that it represents the overall capacity of a muscle to respond to total nerve stimulation and does not allow for a precise analysis of neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in rats, severe atrophy was shown not to occur for at least four months. [49][50][51] Likewise, in rabbits degeneration of muscle tissue did not appear during the first year of denervation. [52][53][54][55] Indeed, our own recent findings show that rat muscle maintains L-type Ca 2+ current and gene expression of the related proteins longer than functional contractile apparatuses.…”
Section: Effects Of Long-lasting Complete Denervation Of Human Musclesmentioning
confidence: 90%